MENGEMBANGKAN NEUROLOGI ANAK USIA DINI DENGAN PEMBELAJARAN BERMAIN WARNA MENGGUNAKAN MEDIA KELERENG - Fitriyani, R. Soelistijanto (PAWIYATAN, 2015)
Childhood is important phase on Human Life Growth. Child is pure personality that is the beginning of Growth Personality byÃÂ Learn Which is Play, Sing a song, and Try. So it means that Chilhood need finest education for make them have a good Growth Personality.Every Education is begin with Pray to Allah.ÃÂ Education for Chilhood must be consist ofÃÂ Cognitive, Afective, Psikomotorik and Pracsis of these. Neorologi is important for Chilhood. It could help Child for thinking, feels and emerge ability. It is good to practive colour playing with use (kelereng).ÃÂ It will help Child to Recognize the Colour and make different of the colour, count the colour and feel that colour is beauty. Students Research which is TittledÃÂ Upaya Meningkatkan Kognitif Anak Melalui Kegiatan Mencampur Warna Dengan Menggunakan Media Kelereng Pada Anak Kelompok B TK Pertiwi Sumberrejo Kabupaten Magelang, had been shown that Colour Playing is Good for Cognitive Emerge even than Brain Abillity Emerge and sense of research by creativeness stimuluss.ÃÂ Key Words: Education,ÃÂ Colour Playing, Neurologi, creativeness, sense of research